2019
DOI: 10.33263/briac96.539546
|View full text |Cite
|
Sign up to set email alerts
|

Solar photovoltaic panels as next generation waste: a review

Abstract: Photovoltaic energy manufacturing has developed at an extraordinary rate since the last decade which globally has reached 225 giga watts by 2018 and is anticipated to augment to 920 giga watts by 2022 and 5000 giga watts by 2050. Still now the abundant quantity of produced solid waste which comes from the end of life panels are not calculated yet but in future it can be a challenging aspect in terms of photovoltaic energy. Harmful waste from end of life solar panels poses a global ecological menace and is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, the contamination of water with these metals can have harmful effects on aquatic creatures, especially algae. PV cells are made of different substances that can be classified into carcinogenic and non-carcinogenic materials [63]. When these substances come into contact with humans or animals via skin adsorption, breathing, or ingestion, they are responsible for tumor formation.…”
Section: Toxicity and Environmental Pollution From Discarded Solar Panelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the contamination of water with these metals can have harmful effects on aquatic creatures, especially algae. PV cells are made of different substances that can be classified into carcinogenic and non-carcinogenic materials [63]. When these substances come into contact with humans or animals via skin adsorption, breathing, or ingestion, they are responsible for tumor formation.…”
Section: Toxicity and Environmental Pollution From Discarded Solar Panelmentioning
confidence: 99%
“…genic and non-carcinogenic materials [63]. When these substances come into contact with humans or animals via skin adsorption, breathing, or ingestion, they are responsible for tumor formation.…”
Section: Toxicity and Environmental Pollution From Discarded Solar Panelmentioning
confidence: 99%
“…Other benefits include zero risk, safe use, low maintenance costs, and high durability [80]. It is forecasted that the PV-powered electricity share will be more than 20% across the world by 2050 [81]. However, Sunanda et al [82] reported that the amount of solid waste produced from the disposal of solar panels has not been accurately determined, and this will become a problem for the photovoltaic energy sector in the future.…”
Section: The Use Of Solar Photovoltaic Systems In Dcsmentioning
confidence: 99%